Reliability worth Assessment of Active Distribution System Considering Protective Devices and Multiple Distributed Generation Units - Subramanya Sarma S; V. Madhusudhan; V. Ganesh (International Journal of Applied Power Engineering (IJAPE), 2018)
Reliability worth assessment is a primary concern in planning and designing of electrical distribution systems those operate in an economic manner with minimal interruption of electric supply to customer loads. Renewable energy sources (RES) based Distributed Generation (DG) units can be forecasted to penetrate in distribution networks due to advancement in their technology. The assessment of reliability worth of DG enhanced distribution networks is a relatively new research area. This paper proposes a methodology that can be used to analyze the reliability of active distribution systems (DG enhanced distribution system) and can be applied in preliminary planning studies to compute the reliability indices and statistics. The reliability assessment in this work is carried out with analytical approach applied on a test system and simulated results validate that installation of distributed generators can improve the distribution system reliability considerably.